Nowe formy wyrazowe dla tradycyjnych znaczeń leksykalnych. O wariantywności słowotwórczej i leksykalnej we współczesnej polszczyźnie (na podstawie badań ankietowych) - Skibski, Krzysztof; Szczyszek, Michał (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The article presents the results of the analyses of the material collected by means of questionnaires, in which the informants are asked to complete a specific meaning of a real lexeme (excerpted from the lexicographical studies into modern Polish) with a linguistic form, which—in the opinion of the respondents—is supposed to be a carrier of a particular meaning. Our aim has been to describe new language signs for traditional meanings of linguistic units. Word-formative structures underwent observation; the analyses were also conducted on the lexical level by probing into the semantic connotations revealed in the answers of the informants. In the answers proposed by the respondents one can notice a marked divergence with regard to both form and semantics. On the level of word formation, the proposals of the respondents often go beyond the semantic boundary—defined by a derivative being an original form—of word formation category. Word-formative formal analysis revealed a multitude of elements by means of which these word formation variants were created (there exists a relationship: the more precise the meaning of the original form, the more word formation variants). Moreover, the lexical analysis demonstrated that the semantic divergence of variants was influenced by the fact that the respondents disposed only of the real meanings of the original forms. The respondents sometimes made an attempt (not very successful) at interpretation of the original definition, taking advantage of, for example, the phenomenon of connotation and association: when an evaluating lexeme appeared in a definition, in the process of categorizing variants there dominated an axiological factor over the semantic one. Additionally, it has been observed that in the case of an imprecise or syntactically complex definition or the one determining a poorly known designate, the phenomenon of structural suggestion is observed: a language user proposed a variant derived from one of the words included in definiendum. The completed observations allow scholars to formulate the following hypothesis: the traditional meanings, known from lexicographical studies, are either not understood or mistakenly interpreted, or, cannot be seen as a point of departure for the study of the semantic and formal structure of the Polish language. Thus, the so-called ordinary users of language may not think about the relationship between reality and its intellectual categorization and a linguistic sign being the culmination of a cognitive processes, and this, in turn, illustrates the standard of their knowledge—a common knowledge.